Community and hospital pharmacists in Europe: encroaching on medicine? - Garattini, Livio (Intern Emerg Med, 2020)
Pharmacy has been historically regarded as a discipline between health and chemistry devoted to drug development, production, and compounding. These tasks have been almost lost with the industrial manufacturing, and dispensing remains the main activity of pharmacists. Hospital pharmacists are usually employees in their workplace, while the professional framework of community pharmacists is very different, being pharmacies predominantly private shops in almost all European countries. In the last years pharmacists have strongly advocated that the focus of their services should switch from ‘product’ to ‘patient’. Clinical pharmacy and pharmaceutical care are the two most cited concepts to support this shift. Clinical pharmacy was originally defined as the area of pharmacy concerned with the science and practice of rational medication use, pharmaceutical care as the responsible provision of drug therapies to achieve definite outcomes. The practice of clinical pharmacy should embrace the philosophy of pharmaceutical care. The new wave of pharmacists’ patient-centered care in Europe still seems to be a reaction against the loss of their traditional professional role after the drug manufacturing revolution. To depict a realistic scenario for progress, it is worth differentiating between hospital and community. Hospital pharmacists should strengthen their pivotal role of medication gatekeepers to improve among clinicians the appropriateness of drug prescriptions and generate savings in expenditures. Any proposal for clinical services provided by community pharmacists is inevitably affected by the issue of their potential remuneration, especially in countries where the remuneration for reimbursable drugs is still a proportion of the retail price.